Design and Implementation of General-Purpose Data Service Platform for Telecom Company - Jun Pan; Jianhe Cheng (Dianxin kexue)
A genera1-purpose data service platform for telecom company based on .NET framework was designed and implemented. The platform carries out the business data cleansing and extraction process and then generates the data mart via ETL tools. System users interact with the data mart via SOA-based data service middleware，which acts as a job scheduler and cube query executer. Particularly，the platform generates a wizard style interface as defined in XML configuration files. Characterized by quick configuration，safeness and flexibility，the system can serve the frontline staffs and senior analytica1 managers at the same time，and has been successfu11y applied in a telecom company.